"Things like tinned burgers and tinned macaroni, I ate as a kid - I would not look at it twice!" Understanding changing eating practices across the lifecourse. (1st January 2020) - McKenzie, John S.; Watts, David
ABSTRACT: There is a common belief that eating patterns acquired during childhood shape them throughout adulthood. However, studies reveal that they can change. This paper explores this contradiction based on interviews with thirty-one people in Scotland. Viewing eating as a social practice, we adopt the lifecourse approach to demonstrate that there is evidence of both continuity and change in eating patterns over time. The concept of dys-appearance reveals why eating patterns are more likely to be revised and when these changes may be reflexively informed by dietary guidelines. This paper reveals that eating patterns acquired in childhood can shape them throughout the lifecourse and be resistant to attempts by others to change them. However, eating patterns may be more likely to change if the impetus for change originates within the individual and revisions are more likely to be informed by dietary guidelines when individuals view their eating patterns as problematic. Thus, this paper not only provides insight into the contradiction highlighted above, but also demonstrates the utility of viewing eating patterns as a social practice whilst illustrating the importance of individual agency in the reproduction of eating patterns, contributes to the sociology of the lifecourse and extends the application of dys-appearance.